2013
DOI: 10.1111/jai.12358
|View full text |Cite
|
Sign up to set email alerts
|

Booster vaccination with live attenuated Vibrio anguillarum elicits strong protection despite weak specific antibody response in zebrafish

Abstract: Summary A live attenuated Vibrio anguillarum vaccine was recently established in the laboratory that induced immunoprotection against vibriosis in zebrafish, Danio rerio. To improve immunogenicity, the effects of different booster vaccination regimens were investigated using bath‐vaccination in a zebrafish model. Zebrafish receiving booster doses at 2 weeks or at both 2 and 4 weeks after primary vaccination were better protected in comparison to fish that received a single vaccination. In addition, the booster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Activation of proinflammatory cytokines is involved in regulating immunoglobulin synthesis in teleosts ( 5 , 7 , 56 ). Zebrafish receiving booster doses of a live attenuated Vibrio anguillarum vaccine at 2 weeks after primary vaccination were better protected against vibriosis in comparison to fish that received a single vaccination ( 57 ). In the current study, we delivered booster immunizations at 2 weeks after primary vaccination to ensure long-term protective immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of proinflammatory cytokines is involved in regulating immunoglobulin synthesis in teleosts ( 5 , 7 , 56 ). Zebrafish receiving booster doses of a live attenuated Vibrio anguillarum vaccine at 2 weeks after primary vaccination were better protected against vibriosis in comparison to fish that received a single vaccination ( 57 ). In the current study, we delivered booster immunizations at 2 weeks after primary vaccination to ensure long-term protective immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Serology upholds animal welfare by sparing pain and discomfort related to the challenge infection while maintaining comparable accuracy at predicting the efficacy of vaccine batches. Some studies have reported low or nil correlation between antibody response and vaccine protection (Thuvander et al 1987;Arnesen et al 2002;Zhang et al 2014). However, the majority of the studies have found a strong correlation (Munday et al 1992;Bricknell et al 1999;Raida et al 2011;Romer Villumsen et al 2012).…”
Section: Application Of Serological Tests In Finfish Health Managementmentioning
confidence: 99%
“…Larvae have to withstand direct exposure to pathogenic bacteria in aquatic environments until the adaptive immune system is formed (Swain & Nayak, 2009;Zhang et al, 2013). Therefore, building immunity through maternal immune transfer in fish should be done to provide larval protection against pathogenic attacks as early as possible (Mingming et al, 2014;Zhang et al, 2014). Maternal immunity transfer can establish broodstock specific and non-specific immunity as well as providing protection to the offspring produced against A. hydrophila bacterial infection (Sukenda et al, 2017).…”
Section: Introductionmentioning
confidence: 99%